Dynamics of Peru’s Position in the Global Copper Ore Trade: A Social Network Analysis - Aguinaga Fonseca, María Valeria (2024)
This thesis delves into Peru’s dynamic role within the global copper ore trade network amidst escalating demand and concentrated production. It navigates Peru’s evolving export position, examines its response to shifting export values and trade partners, and evaluates its influence on the global copper ore trade network for over a decade. Through Social Network Analysis (SNA), this study reveals Peru’s remarkable resilience as a leading copper ore exporter from 2013 to 2022, as illustrated by its stable normalised out-degree and high betweenness centrality, which affirms its strategic role as an intermediary and influencer in trade flows. The findings underscore Peru’s growing interconnectedness with its trade partners, bolstered by an increasing clustering coefficient, indicating robust and direct trade relationships. However, the rise of competitors, specifically Indonesia and Brazil, introduces new challenges and requires strategic adjustment. The research concludes that Peru’s significant role in the global copper ore network is characterised by its adept navigation of market fluctuations and competitive pressures. This study provides critical insights into the dynamics of the copper ore trade market for policymakers, economists, and industry stakeholders. This enriches our understanding of Peru’s key position in the global copper industry, its contributions to energy transition, and its strategic international interactions. The strategic implications highlight the necessity for diversification, strengthening diplomatic relations, and implementing risk mitigation strategies to preserve and augment Peru’s status as a preeminent copper exporter. These insights and recommendations aim to guide sustainable resource management and foster resilient international trade relations in a rapidly evolving global market.